Alteration of Vestibular Function in Pediatric Cochlear Implant Recipients - Koyama, Hajime; Kashio, Akinori; Fujimoto, Chisato; Uranaka, Tsukasa; Matsumoto, Yu; Kamogashira, Teru; Kinoshita, Makoto; Iwasaki, Shinichi; Yamasoba, Tatsuya (Frontiers in Neurology, 2021)
Background: Vestibular dysfunction is a complication of cochlear implantation (CI). Reports on the evaluation of vestibular function before and after CI are limited, especially in children. We investigated the effect of CI on vestibular function in pediatric patients. Patients and methods: We routinely evaluated vestibular function before but not immediately after CI. Therefore, patients who underwent sequential bilateral CI were enrolled in this study. Seventy-three children who underwent sequential CI from 2003 to 2020 at our hospital were included. Since the vestibular function of the first implanted ear was evaluated before the second surgery for the contralateral ear, post-CI evaluation timing differed among cases. The evaluation included a caloric test, a cervical vestibular evoked myogenic potential (cVEMP) test, and a damped rotation test. The objective variables included the results of these tests, and the explanatory variables included the age at surgery, cause of hearing loss, electrode type, and surgical approach used. The correlations of these tests were analyzed. Results: cVEMP was the most affected after CI (36.1%), followed by the caloric test (23.6%), and damped rotation test (7.8%). Cochleostomy was significantly more harmful than a round window (RW) approach or an extended RW approach based on the results of the caloric test (p = 0.035) and damped rotation test (p = 0.029). Perimodiolar electrodes affected the caloric test results greater than straight electrodes (p = 0.041). There were no correlations among these tests’ results. Conclusions: Minimally invasive surgery in children using a round window approach or an extended round window approach with straight electrodes is desirable to preserve vestibular function after CI.